2020
DOI: 10.3390/polym12071608
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Improved Thermal and Dielectric Performance of Epoxy Composites Containing Ti3C2Tx Platelet Fillers

Abstract: Polymer composites with enhanced thermal and dielectric properties can be widely used in electric and energy related applications. In this work, epoxy composites have been prepared with Ti3C2Tx, one of the most studied MXene materials that can be massively produced by direct etching using hydrofluoric acid. The addition of conductive two dimensional Ti3C2Tx platelet fillers leads to improved but anisotropic thermal conductivity of the composites. The through-plane thermal conductivity reaches 0.583 Wm−1K−1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our MXene can operate for four hours at full speed, the cost per unit of energy is $0.081, and the maximum capacity of the ball milling jar is 250 grams. Therefore, the cost per gram of mass produced by this machine is readily calculable using equation (1).…”
Section: Ball Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our MXene can operate for four hours at full speed, the cost per unit of energy is $0.081, and the maximum capacity of the ball milling jar is 250 grams. Therefore, the cost per gram of mass produced by this machine is readily calculable using equation (1).…”
Section: Ball Millingmentioning
confidence: 99%
“…Since scientists have realized the potential of MXene, a great deal of research has been published on it recently. Since the first successful discovery of MXene, it has been observed that most studies focus on Ti3C2Tx [1]. The research community has heavily reviewed, discussed, and studied the synthesis procedures, involved synthesis parameters, types of etching processes, and safety protocols related to the synthesis of MXene from its precursors, the so-called MAX phases [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nanomaterials may enhance both TC and fire safety. In recent years, different studies affirm that TC may be improved by incorporating MXenes to the ER, often reaching better results than other 2D nanofillers [ 28 , 49 , 50 ]. Most of the works focused on obtaining oriented composites to enhance thermal conductivity, so anisotropic conductivity was observed.…”
Section: Properties and Applications Of Mxene/epoxy Compositesmentioning
confidence: 99%
“…In consequence, depending on the preparation method of the nanocomposite, the distribution of MXene sheets may be improved and increase the anisotropic conductivity. Lin et al aligned the filler distribution by shear and centrifugal force in stirring by cast-moulding [ 50 ]. Due to the aligned distribution of the filler, the in-plane TC was improved, even for the samples with less MXene reinforcement, 6.45 times better than the same sample of 5% MXene without alignment.…”
Section: Properties and Applications Of Mxene/epoxy Compositesmentioning
confidence: 99%
“…[33] In a work by Chen et al, they reported the improvement in electrical, dielectric, and thermal properties of an epoxy composite containing MXenes platelets. [34] Feng et al added 1.2 wt% of MXenes into the commercial epoxy system and reported good electrical conductivity (4.52 × 10 −6 S cm −1 ) and moderate tensile strength (66.2 MPa). [35] Anti-friction, anti-corrosive, hightoughness, low-creep, improved electromagnetic interference (EMI) shielding, wettability, and shear strength are some of the advantages reported of MXenes-filled thermosetting composites.…”
Section: Introductionmentioning
confidence: 99%